Adherence to sleep recommendations is associated with higher satisfaction with life among Norwegian adolescents - Erik Grasaas; Sergej Ostojic; Henriette Jahre (BMC, 2024)
Abstract Background Sleep plays a crucial role in the health and well-being of adolescents; however, inadequate sleep is frequently reported in numerous countries. This current paper aimed to describe sleep duration, factors impacting sleep, consequences of insufficient sleep and satisfaction with life in Norwegian adolescents, stratified by sex and by adherence to the 8-hour sleep recommendation, and to examine potential associations between adherence to the 8-hours sleep recommendation and satisfaction with life. Methods This is a cross-sectional study using data from the Norwegian Ungdata Survey, collected in 2021. Adolescents from five Norwegian counties were included, comprising a total of 32,161 upper secondary school students. Study variables were collected through an electronic questionnaire administered during school hours and all data are anonymous. Descriptive data of sleep patterns are presented, and linear regressions were conducted adjusting for SES, perceived stress, physical activity level, over-the-counter analgesics use, grade level and screen time. Results 73% of adolescents did not adhere to the 8-hours of sleep recommendation per night, with similar results for girls and boys. 64% reported tiredness at school (minimum 1-2 days weekly) and 62% reported that screen time negatively affected their ability to sleep. 23% reported that gaming affected their sleep, with a higher prevalence in boys than girls. Satisfaction with life score was 7.0 ± 1.9 points (out of 10) for the total sample, with higher scores for boys (7.3 ± 1.8 points) than girls (6.9 ± 1.9 points). Regressions revealed a positive association with satisfaction with life (B = 0.31, 95% [0.15 to 0.48]) in adolescents adhering to sleep recommendation of 8h compared to the ones not adhering to the sleep recommendation. Conclusions Most Norwegian adolescents fail to adhere to the 8-hours of sleep recommendation and the majority feel tired at school or during activities. More than half of adolescents reported that screen time negatively affected their ability to sleep. Adhering to the sleep recommendation was associated with higher life satisfaction. Our findings highlight the importance of sufficient sleep in adolescents, while future research is needed to examine other sleep related measures on adolescents´ satisfaction with life.